Biological invasions and pollinator decline - Montero Castaño, Ana (2018)
Here, we review the mechanisms through which animal and plant invasive species may affect pollinators, either directly or indirectly. We classified these mechanisms in four groups: (a) changes in habitat quantity or quality, (b) predation, (c) pathogen spread and (d) genetic introgression. We review the impacts of these mechanisms on the behaviour, demography and evolution of native pollinators and their communities. In addition, we highlight some current knowledge gaps about the effect of biological invasions on pollinators and suggest some measures to minimize such effects.